2019
DOI: 10.1080/09670262.2019.1668062
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofMartensia(Delesseriaceae; Rhodophyta) from shallow and mesophotic habitats in the Hawaiian Islands: description of four new species

Abstract: Fifty-six specimens of the red algal genus Martensia from the Main and Northwestern Hawaiian Islands, representing both shallow (36 specimens from 0-20 m depth) and mesophotic habitats (20 specimens from 62-93 m depth), were collected and characterized using morphological and molecular analyses. Phylogenetic analyses of the rbcL gene resolved five distinct clades of Martensia from the Hawaiian Islands, of which none could be attributed to the two previously used taxonomic names for this flora (M. fragilis Harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For example, one of four new sea lettuces was closely allied with an undescribed taxon from the Kermadec Islands and western Australia, two were closely associated with specimens from Mage Island, Japan, and the fourth species was not closely associated with any other known sea lettuce species (Spalding et al 2016). A recent analysis of the red algal genus Martensia from Hawai'i revealed the presence of five species, all with mesophotic representation, four of which were newly described in the study and presumed endemic to the Hawaiian Islands, and one that was demonstrated to be a new record for the islands (M. albida Y. Lee) and previously known only from Korea (Sherwood et al 2019). Two new species described in the peyssonnelioid genus Ramicrusta from Lehua Island, Hawai'i (one from mesophotic depths) were distinct from all other described species thus far but were allied with taxa known from the western Pacific / Australasia and the Caribbean (Sherwood et al in press).…”
Section: Discussionmentioning
confidence: 69%
“…For example, one of four new sea lettuces was closely allied with an undescribed taxon from the Kermadec Islands and western Australia, two were closely associated with specimens from Mage Island, Japan, and the fourth species was not closely associated with any other known sea lettuce species (Spalding et al 2016). A recent analysis of the red algal genus Martensia from Hawai'i revealed the presence of five species, all with mesophotic representation, four of which were newly described in the study and presumed endemic to the Hawaiian Islands, and one that was demonstrated to be a new record for the islands (M. albida Y. Lee) and previously known only from Korea (Sherwood et al 2019). Two new species described in the peyssonnelioid genus Ramicrusta from Lehua Island, Hawai'i (one from mesophotic depths) were distinct from all other described species thus far but were allied with taxa known from the western Pacific / Australasia and the Caribbean (Sherwood et al in press).…”
Section: Discussionmentioning
confidence: 69%
“…2020, Sherwood et al. 2020, 2021), including the red alga Dissimularia withallii from Jarvis Island, Northern Line Islands (Kraft and Saunders 2014). The new genus and species Brilliantia kiribatiensis adds to our knowledge of endemic species in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological plasticity, intraspecific variation in form due to environmental differences, makes identifying specimens difficult [33][34][35][36][37]. Similarly, different species with convergent morphologies are difficult to distinguish [38][39][40]. These dilemmas are not confined to any particular taxon or region, but to various macroalgae worldwide.…”
Section: Discussionmentioning
confidence: 99%